Single Nucleotide Polymorphisms in PPARD Associated with Systemic Lupus Erythematosus in Chinese Populations - Yuan-yuan Qi; Ya-ling Zhai; Xin-ran Liu; Xiao-xue Zhang; Ya-fei Zhao; Xiang-hui Ning; Zhan-Zheng Zhao (Journal of Immunology Research)
Background. Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disease characterized by apoptotic clearance deficiency provoking autoimmune responses and leading to multiple organ damage. PPAR-δ, encoded by the PPARD gene, was induced in macrophages promoting the timely disposal of apoptotic cells. Biological studies had provided solid foundation of PPARD involvement in SLE; it is worthwhile to further explore the genetic contribution of PPARD to SLE. Methods. We performed a discovery-replication genetic association study. The discovery study was based on previous reported GWAS data. And the replication study was conducted in 1003 SLE patients and 815 healthy controls from Henan, Middle East of China. Further, we analyzed the eQTL effect to identify possible functional significance. Results. In the genetic association analysis, we observed significant association between the risk C allele of rs4713853 (p=0.03, OR 1.167, 95% CI 1.015-1.341) and increased SLE susceptibility. Moreover, individuals with the risk C allele were associated with lower expression of PPARD and DEF6. Our clinical analysis showed that SLE patients with the risk C allele of rs4713853 were more likely to present a higher proportion of anti-Sm antibody presence (CC+CT vs. TT, 20.0% vs. 14.2%, p=0.039) and higher level of Scr (median inter quarter range CC+CT vs. TT, 56 48-71 vs. 54 46-64 μmol/L, p=0.002). Conclusions. In conclusion, our study identified a novel association between PPARD rs4713853 and SLE susceptibility in Chinese populations. By integrating multiple layers of analysis, we suggested that PPARD might be a main candidate in the pathogenesis of SLE.